The Antimicrobial Activities of Extract and Compounds Isolated from Brillantaisia lamium - Jean De Dieu Tamokou; Jules Roger Kuiate; Mathieu Tene; Timothée Julbelin Kenla Nwemeguela (Iranian Journal of Medical Sciences, 2011)
Background: Brillantaisia lamium is an erect branched herb, which grows to a height of 1.50 m in moist tropical areas, both in full sun and partial shade. In Cameroon, the aerial part of this plant is used in the treatment of various microbial infections such as skin diseases and infections of urinary tract. The aim of this study was to evaluate the antimicrobial activities of CH2Cl2: MeOH (1:1) extract, fractions and compounds from the aerial part of B. lamium. Methods: The plant was dried and extracted by maceration in CH2Cl2: MeOH (1:1 v/v). Structures of the compounds from the CH2Cl2: MeOH (1:1) soluble fraction were determined by spectroscopic methods and compared with published data. The broth micro dilution method was used to evaluate the antimicrobial activities against bacteria and fungal species. Results: Four known compounds: aurantiamide acetate (1), lupeol (2), lespedin (3), sitosterol 3-O-β-D-glucopyranoside (4) and a mixture of sterols: campesterol (5), stigmasterol (6) and β-sitosterol (7) were isolated from CH2Cl2: MeOH (1:1) extract of B. lamium aerial parts. The crude extract, fractions and isolated compounds exhibited both antibacterial and antifungal activities that va-ried with microorganism (MIC=6.25 – 1000 µg/ml). Compound 3 was the most active (MIC=6.25 – 100 µg/ml) while Staphylococcus aureus, Enterococcus faecalis, Candida tropi-calis and Cryptococcus neoformans were the most sensitive to all the tested compounds. Conclusion: The overall results of this study indicate that the CH2Cl2: MeOH (1:1) extract and some of isolated compounds have interesting antimicrobial properties and can be used for the treatment of fungal and bacterial infections